The Real Effects of Mobile Money : Evidence from a Large-Scale Fintech Expansion - Patnam, Manasa; Yao, Weijia (Washington, D.C. : International Monetary Fund, 2020)
Mobile money services have rapidly expanded across emerging and developing economies and enabled new ways through which households and firms can conduct payments, save and send remittances. We explore how mobile money use can impact economic outcomes in India using granular data on transactions from Paytm, one of the largest mobile money service provider in India with over 400 million users. We exploit the period around the demonetization policy, which prompted a surge in mobile money adoption, and analyze how mobile money affects traditional risk-sharing arrangements. Our main finding is that mobile money use increases the resilience to shocks by dampening the impact of rainfall shocks on nightlights-based economic activity and household consumption. We complement these findings by conducting a firm survey around a phased targeting intervention which incentivized firms to adopt the mobile payment technology. Our results suggest that firms adopting mobile payments improved their sales after six-months of use, compared to other firms. We also elicit firms' subjective expectations on future sales and find mobile payment adoption to be associated with lower subjective uncertainty and greater sales optimism.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet